Isolation of Kerstersia gyiorum from a patient with cholesteatomatous chronic otitis media - Almuzara, Marisa N. (2012)
We describe the first case of a Kerstersia gyiorum strain isolated from a patient with cholesteatomatous chronic otitis media. We emphasize the isolation of members of the family Alcaligenaceae in serious infections and unusual sites and the importance of polyphasic identification addressing the definitive identification. Copyright © 2012, American Society for Microbiology. All Rights Reserved.